Association Between Exercise and Low Back Pain Resulting in Modified Duty and Lost Time: A Cross-Sectional Analysis of an Occupational Population. Issue 10 (October 2018) - Walker, Skyler D.; Brown, Holden L.; Thiese, Matthew S.; Ott, Ulrike; Wood, Eric; Kapellusch, Jay; Hegmann, Kurt T.
Abstract : Objective: The aim of the study was to assess the relationship between leisure time exercise and whether workers ever had modified duty or lost time (MD/LT) due to low back pain (LBP) in an occupational cohort. Methods: Workers ( N = 827) completed a structured interview assessing characteristics of their LBP, whether or not the pain caused modified or lost work time, and their participation in leisure time exercise. Odds ratio of modified/lost time and minutes of exercise participation were assessed. Results: Workers who participated in over 316 min/wk of leisure time exercise incurred significantly less modified/lost time, adjusted odds ratio = 0.46 (95% confidence interval, 0.23 to 0.98). There also lies a significant trend between increases in leisure time exercise and reductions in modified/lost time ( P = 0.0016). Conclusion: These results suggest exercise reduces risk of MD/LT from LBP.